2002
DOI: 10.1046/j.1365-2427.2002.01004.x
|View full text |Cite
|
Sign up to set email alerts
|

0+ perch predation on 0+ bream: a case study in a eutrophic gravel pit lake

Abstract: SUMMARY 1. We studied the population dynamics of 0+ fish in a eutrophic gravel pit lake in which predation of 0+ Eurasian perch on other 0+ fish was suspected to influence perch growth and the structure of the fish community, with effects on the lake food web. 2. The adult fish community was dominated by piscivorous species, especially perch, and the 0+ fish community was dominated by perch and bream. Bream grew to a total length of 80 mm between May and the end of August, gradually decreased in numbers during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
125
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(132 citation statements)
references
References 48 publications
(61 reference statements)
7
125
0
Order By: Relevance
“…Some authors demonstrated that growth of 0+ fish increases significantly when they switch from zooplanktivorous or benthivorous feeding to piscivory (Van Densen 1985;Buijse and Houthuijzen 1992;Olson 1996;Borcherding et al 2000). As recently shown by Beeck et al (2002), early piscivory of 0+ perch, starting with a mean size of 28 mm in total length (TL), not only increases individual growth, but also leads to a bimodal size distribution, with fast-growing piscivores and slow-growing zooplanktivores.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some authors demonstrated that growth of 0+ fish increases significantly when they switch from zooplanktivorous or benthivorous feeding to piscivory (Van Densen 1985;Buijse and Houthuijzen 1992;Olson 1996;Borcherding et al 2000). As recently shown by Beeck et al (2002), early piscivory of 0+ perch, starting with a mean size of 28 mm in total length (TL), not only increases individual growth, but also leads to a bimodal size distribution, with fast-growing piscivores and slow-growing zooplanktivores.…”
Section: Introductionmentioning
confidence: 99%
“…Persson 1993). In addition to the aforementioned food of 0+ perch, there have also been a few reports of piscivorous 0+ perch (Clemens et al 1924;Smyly 1952;Mehner et al 1996;Beeck et al 2002). Some authors demonstrated that growth of 0+ fish increases significantly when they switch from zooplanktivorous or benthivorous feeding to piscivory (Van Densen 1985;Buijse and Houthuijzen 1992;Olson 1996;Borcherding et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Variation in the timing of diet shifts can thus be hypothesised to result in diVerent degrees of size variation within cohorts depending on the relative size-dependent resource proWtability in diVerent niches, ultimately leading to bimodal size distributions (e.g. Beeck et al 2002). Furthermore, variation in YOY Wsh densities has been shown to aVect resource densities (Byström and Garcia-Berthou 1999;Persson et al 2000a).…”
Section: Introductionmentioning
confidence: 99%
“…The perch's improved growth in Lake Piediluco, in comparison with the years in which the lake was mesotrophic, is also due to the fact that the diet of this species is currently broader and includes more fish than formerly (GIOVINAZZO, 1988). Indeed, an increase in fish-eating is strongly correlated with an improvement in growth (THORPE, 1977;BEECK et al, 2002;HOLMGREN, 2003).…”
Section: Discussionmentioning
confidence: 99%